THE IMPACT OF INFORMATION TECHNOLOGIES ON DISTANCE EDUCATION DURING PANDEMIC IN THE REPUBLIC OF UZBEKISTAN - Elza Salakhova , Manzura Shamsitdinova , Mavjuda Shakhakimova (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Today there is a huge selection of educational programs. Anyone can sign up for online courses on interests, go through various distance programs. This format allows a huge number of people to master their favorite specialty who do not have enough time and money to obtain higher education in the traditional way. Especially online education is relevant in light of recent events, when the world is gripped by a pandemic. For online learning, one can choose any suitable format, these are online webinars or Skype conferences, and etc. Therefore, the impact of Information Technology on distance education is very vital. The possibilities of IT in the implementation of distance learning are endless. Therefore, the effectiveness of distance education depends on how well the information technologies developed in the country and how well people can use possibilities of information technologies in online learning. The authors of the article are trying to make an overview of distance learning during a pandemic in the Republic of Uzbekistan. They analyze distance learning in general and on the example of a university, as well as some of the advantages and disadvantages of this type of education from personal experience in this format of education at a university.